MODUL PERSEDIAAN KERJAYA MURID BERKEPERLUAN KHAS KE ARAH MEMENUHI PASARAN PEKERJAAN BIDANG JAHITAN PEMBUAT PAKAIAN LELAKI (Proceedings of International Conference on Special Education, 2019)
In line with the development of education that is always in line with the technological advancement, for example now the development towards the revolutionary industry 4.0, special needs students also need to acquire the knowledge and skills that enable them to be ready to go to the world of work. The study aims to explore and produce best practice guidelines using a career-preparing module approach in the field of sewing industry especially manufacturing of men's clothing. The method of data collection is to use document analysis as the main data, in addition to interviews and physical observations as support data. The study participants consisted of five special needs students who attended the men's clothing manufacturing course. The findings show that exposure-related activities and career experience in stitches, preparation for career and parental involvement help in generating this module. The findings also show that teachers need to apply skills to students with special needs in ensuring the modules are well implemented. The production of career preparation modules in this stitch field is expected to help these special needs students to explore further in the field of tailoring especially in the field of men's clothing. This is because these studies have implications for the preparation of appropriate work skills in the field of stitches based on the strengths and abilities of special needs students.